2016
DOI: 10.1039/c6ay00324a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bisphenols in environmental water samples using polydopamine-coated magnetic Fe3O4 as a magnetic solid-phase extraction material coupled with high-performance liquid chromatography

Abstract: Fe3O4@polydopamine composites were synthesized and used as a magnetic adsorbent to extract bisphenols from environmental water samples before determination using HPLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Deposition of thin films from organic molecules or polymers is an increasingly used strategy to confer specific physical or chemical properties to materials and devices for a variety of biomedical and technological applications. , A paradigm methodology in this context relies on polydopamine (PDA), a eumelanin-like material with universal adhesion and coating properties inspired to catechol- and amine-rich mussel byssus proteins . By dip-coating into a dopamine solution in Tris buffer at pH 8.5 , it is possible to functionalize and modify virtually any surface, enabling conjugation with biomolecules to obtain biomaterials for tissue engineering and surface tailoring for energetic, environmental, and analytical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of thin films from organic molecules or polymers is an increasingly used strategy to confer specific physical or chemical properties to materials and devices for a variety of biomedical and technological applications. , A paradigm methodology in this context relies on polydopamine (PDA), a eumelanin-like material with universal adhesion and coating properties inspired to catechol- and amine-rich mussel byssus proteins . By dip-coating into a dopamine solution in Tris buffer at pH 8.5 , it is possible to functionalize and modify virtually any surface, enabling conjugation with biomolecules to obtain biomaterials for tissue engineering and surface tailoring for energetic, environmental, and analytical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, it has been reported that BPs exhibit estrogenic and carcinogenic activities. 5,6 Therefore, there is universal concern regarding the presence of these endocrine-disrupting compounds in the environment. 7…”
Section: Introductionmentioning
confidence: 99%
“…This includes the use of novel sorbents, including amino-functionalized metal–organic frameworks, 7,9,28 hollow porous carbon spheres, 29,30 molecularly imprinted polymers, 8,13,17 magnetic cellulose-based carbon fibers, 31 polymer micro- and nanofibers, 32 and dopamine-coated magnetic sorbent. 6…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic adsorbents play an important role in the MSPE of various analytes, causing many researchers to focus on exploring novel MSPE adsorbents . Multiple magnetic materials have been used to extract trace bisphenols from environmental water samples, such as Fe 3 O 4 /graphene quantum dots (Fe 3 O 4 /GQDs) magnetic nanocomposite , iron‐ferric oxide/graphene oxide composite (Fe@Fe 2 O 3 /GO) , polydopamine‐coated magnetic Fe 3 O 4 composites (Fe 3 O 4 @PDA) , and ionic liquid (IL) coated magnetic Fe 3 O 4 nanoparticles (NPs) . However, the most magnetic sorbents are based on iron oxides that are vulnerable under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%